Densitometric HPTLC quantification of asiaticoside isolated from Centella asiatica (L.) Urb (Apiaceae) of Benin - GANSE, Hippolyte; Gbaguidi, A. Fernand; AGBANI, Pierre O.; JOSSE, Roger G.; MOUDACHIROU, MANSOUROU; Sinsin, Brice A.; Quetin-Leclercq, Joëlle; AMINOU, Taofiki (My University, 2010)
Asiaticoside isolated from Centella asiatica has been found through in vitro test to serve as an active agent of healing on wounds. To quantify this compound in Centella asiatica cultivated in Benin, a new, simple and rapid High-Performance Thin-Layer Chromatography (HPTLC) method was developed and validated for its selectivity, its recovery, and its repeatability. Compounds have been separated on silica gel 60F254 plates with ethyl acetate/methanol/water (100/25/10, v/v/v), as mobile phase. The detection was done by densitometry scanning at λ = 600 nm and the calibration plots showed that the graphical response was linear and dependent on the quantity in the range of 2.50- 12.50 µg, with good values of R² = 0.998. This method is repeatable and precise with relative standard deviations between1.42 and 5.92% for the intra-day tests and between 1.27 and 6.57% for the inter-day tests for the quantities belonging to an interval of 2.50 and 12.50 µg. The limits of detection and quantification were 0.317 and 1.05 µg respectively. The quantity of asiaticoside found was 0.24% in the alcoholic extract.
Keywords: HPTLC; Centella asiatica; Asiaticoside; Wounds.